Mechanical properties of engineered cementitious composites using local ingredients / Lee Siong Wee...[et al.] - Lee, Siong Wee; Oh, Chai Lian; Md Zain, Mohd Raizamzamani (Faculty of Mechanical Engineering Universiti Teknologi MARA (UiTM), 2019)
This research focuses on the mechanical properties of Engineered Cementitious Composites (ECC). Few ECC mixtures were designed and tested under direct tensile test and compression test. The novelty of this research is the utilization of available local materials in Malaysia, which is significantly different from the ingredients employed by previous researchers in the US, Japan and other countries. The ingredients used for ECC mixtures in this research were Ordinary Portland Cement (OPC), ground granulated blast-furnace slag (GGBS), sand, water, superplasticizer (SP) and polypropylene (PP) fibers. Local ingredients such as river sand and GGBS were used to replace micro silica sand and fly ash in the standard mix of ECC. Test results demonstrated that tensile ductility and compressive strength in ECC improved as compared to normal concrete. The effect of cement replacement ratio and fibres content are discussed based on the performance in both tensile and compressive properties. Comparison with previous studies was carried out to identify the weaknesses of the current ECC mixture, so that improvement can be done in future studies. The best ECC mixture is proposed according to the performance in mechanical properties.